Anxiety Sensitivity and Distress Tolerance in Smokers: Relations With Tobacco Dependence, Withdrawal, and Quitting Success. Issue 1 (6th May 2019) - Schlam, Tanya R; Baker, Timothy B; Smith, Stevens S; Cook, Jessica W; Piper, Megan E
Abstract: Introduction: This study examined relations of two affective vulnerabilities, high anxiety sensitivity (AS) and low distress tolerance (DT), with tobacco dependence, withdrawal, smoking cessation, and pharmacotherapy response. Methods: Smokers interested in quitting ( N = 1067; 52.2% female, 28.1% African American) were randomized to 12 weeks of nicotine patch, nicotine patch plus nicotine lozenge, or varenicline. Baseline questionnaires assessed AS, DT, negative affect, anxiety, and dependence. Withdrawal was assessed the first-week post-quit via ecological momentary assessment. Results: DT, but not AS, predicted biochemically confirmed point-prevalence abstinence at multiple endpoints: weeks 4, 12, 26, and 52 post-quit ( p s < .05); relations remained after controlling for pharmacotherapy treatment, AS, baseline negative affect, anxiety, and anxiety disorder history ( p s < .05). Additional exploratory analyses examining week 4 abstinence showed DT predicted abstinence ( p = .004) even after controlling for baseline dependence, post-quit withdrawal (craving and negative affect), and treatment. DT moderated treatment effects on abstinence in exploratory analyses (interaction p = .025); those with high DT were especially likely to be abstinent at week 4 with patch plus lozenge versus patch alone. Conclusions: DT, but not AS, predicted abstinence over 1 year post-quit (higher DT was associated with higher quit rates), with little overlap with other affective measures. DT also predicted early abstinence independent of dependence and withdrawal symptoms. Results suggest low DT may play a meaningful role in motivation to use tobacco and constitute an additional affective risk factor for tobacco cessation failure beyond negative affect or clinical affective disorders. Implications: People in a stop-smoking study who reported a greater ability to tolerate distress were more likely to quit smoking and remain smoke-free 1 year later. Smokers with high DT were more likely to be smoke-free 4 weeks after their target quit day if they received nicotine patch plus nicotine lozenge rather than nicotine patch alone. Trial Registration: NCT01553084.